1988
DOI: 10.1111/j.1365-2362.1988.tb02408.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered bile acid profiles in duodenal bile and urine in diabetic subjects

Abstract: The bile acid composition in duodenal bile was analysed in 22 diet-treated and 11 insulin-treated middle-aged patients with diabetes mellitus and in 20 normoglycaemic controls. In 10 subjects with diabetes mellitus the bile acid profile in urine was also investigated. In the non-insulin-dependent diabetic patients the percentage of cholic acid was reduced and that of deoxycholic acid increased. As a highly significant finding there was a three-fold increase of the percentage of 12-ketolithocholic acid in duode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 28 publications
5
36
0
1
Order By: Relevance
“…5). This has important implications in diabetes therapy as work in our laboratory has confirmed the distal GIT to be the site of intended drug delivery due to an abundance of efflux transporters, which have been associated with PB absorption after oral administration, such as the transporter ABCA1 (37,38). However, the exact impact of such release patterns in PB oral absorption, efficacy and safety profiles remains difficult to predict (39)(40)(41).…”
Section: Drug Release Studies and In Vitro Dissolutionmentioning
confidence: 94%
“…5). This has important implications in diabetes therapy as work in our laboratory has confirmed the distal GIT to be the site of intended drug delivery due to an abundance of efflux transporters, which have been associated with PB absorption after oral administration, such as the transporter ABCA1 (37,38). However, the exact impact of such release patterns in PB oral absorption, efficacy and safety profiles remains difficult to predict (39)(40)(41).…”
Section: Drug Release Studies and In Vitro Dissolutionmentioning
confidence: 94%
“…Indeed, Brufau et al showed that patients with type 2 diabetes exhibited increased concentrations of deoxycholic acid and decreased concentrations of chenodeoxycholic acid, which was due to the increased synthesis rate of cholic acid and deoxycholic acid. Other human studies have found similar changes in the bile acid pool in diabetes, but these studies are difficult to interpret in a comparative manner due to different methodologies and study populations (131,136,136,137,138). Recently, Haeusler et al have reported that there might be a plausible, mechanistic explanation for diabetes-related changes in the bile acid pool composition involving Forkhead box protein 01 (FOX01 (FOXP1)), a transcription factor regulating gluconeogenesis, glycogenolysis and liver sensitivity to insulin (140,146).…”
Section: Bile Acid Pool Composition Is Altered In Type 2 Diabetesmentioning
confidence: 99%
“…Subsequently, changes in bile acid pool composition have been demonstrated in both animal models of type 1 diabetes and type 2 diabetes, respectively (132,133,134,135), as well as in early (131,136,137,138,139) and recent human studies (22, 111, 121, 140). Of note, both glucose (141) and insulin have been suggested to modulate bile acid synthesis in preclinical studies (135,142,143) and in some (131,138,144), but not all (137), clinical studies. As noted by Staels & Fonseca, the finding that insulin is able to suppress FXR (NR1H4) gene expression (in contrast to glucose, which produces the opposite effect) suggests that diabetes is associated with the dysregulation of FXR expression (141,145).…”
Section: Bile Acid Pool Composition Is Altered In Type 2 Diabetesmentioning
confidence: 99%
“…Bile acids are also signaling molecules that activate bile acid receptors to regulate bile acid synthesis and glucose metabolism (2). In vivo studies show that bile acid pool and excretion increase in diabetic human patients (3,4) and in experimental diabetic animals (5,6). Insulin treatment restores bile acid pool and synthesis to the normal levels.…”
mentioning
confidence: 99%